Determination of the Henry's law constants of low-volatility compounds via the measured air-phase transfer coefficients. (1st September 2017) - Chao, Huan-Ping; Lee, Jiunn-Fwu; Chiou, Cary T.
Abstract: Accurate Henry's law constants ( H ) are unavailable for the majority of organic pollutants, especially those having a low volatility. A novel kinetics-based experimental method is introduced to determine H for a wide range of low- H compounds. The method consists of measuring independently the water-to-air transfer coefficient ( K L ) and the associated air-phase transfer coefficient ( k G ) of a low- H chemical (solute) in water when K L ≅ k G H prevails according to the two-film theory. The k G for a solute is obtained via a developed gas-dynamic equation that relates k G to the solute molecular weight and the solute-vapor escaping efficiency ( β ) through a boundary air layer. The value of β is only a function of the in situ air turbulence level, independent of the chemical species. Thus, the required β for solutes can be estimated from the evaporative rates of pure volatile liquids under the same ambient setting. By relating the estimated k G with the measured K L of a low- H solute, the solute H is established. The H values of 45 low- H chemicals, including many complex pesticides, in the range of ∼10 −7 to ∼10 −3 have thus been determined. The accountability of the method is underscored by the consistency of the measured and credible literature H values for a number of the low- H compounds studied. Graphical abstract: Highlights: A kinetic method is developed to measure the Henry's law constants ( H ) of low- H chemicals. Solute volatilization coefficient ( K L ) and air-phase transfer coefficient ( k G ) are determined. The k G of a chemical is estimated via a novel vapor-dynamic equation. Coupling K L with k G enables H to be determined based on the two-film theory.